2023
DOI: 10.1108/et-08-2022-0295
|View full text |Cite
|
Sign up to set email alerts
|

Impact of quality assurance on TVET programs for the digital employment market of IR 4.0 in Pakistan: a quantitative investigation

Abstract: PurposeIn the current period quality assurance (QA) and technical vocational education and training (TVET) are known as the two comprehensively examined ideas in schooling, dependent on exceptional abilities in this modern era of Industrial Revolution (IR) 4.0. The incapability or need for QA of technology-oriented programs has been dissected by policy makers as a hindrance in accomplishing the TVET objectives. Consequently, the reason for this exploration paper was to contemplate over the impact and associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…For example, a study found that women are encouraged by family members to pick professions that they can work from their own homes. [25] The safe and secure environment was another factor mentioned by research. Parents were unwilling to send their female children to institutes far from their homes.…”
Section: Gender Inequalitiesmentioning
confidence: 99%
“…For example, a study found that women are encouraged by family members to pick professions that they can work from their own homes. [25] The safe and secure environment was another factor mentioned by research. Parents were unwilling to send their female children to institutes far from their homes.…”
Section: Gender Inequalitiesmentioning
confidence: 99%